Iso-conversional kinetic and thermodynamic studies of Indian sagwan sawdust pyrolysis for its bioenergy potential - Gupta G.K.; Mondal M.K. (My University, 2025)
Thermochemical conversion of biomass for bio-energy production is a potential option where condensable fractions can be utilized as fuel or for valuable chemicals and residual fractions for syngas (CO + H2) production. Present study aims at investigating the physicochemical properties and pyrolysis kinetics of Indian sagwan sawdust degradation using thermogravimetric analyzer at three heating rates (5, 10, and 20 K/min). Physical and chemical properties of ISS were determined by proximate, ultimate, compositional analysis, FTIR, XRD, and higher heating value. TGA results showed maximum devolatilization took place in the temperature range of 480–750 K. Three different iso-conversional models Flynn–Wall–Ozawa, Kissinger–Akahira–Sunose, and Friedman methods were applied on TGA results to calculate the activation energy and pre-exponential factors. Average activation energies from FWO, KAS, and Friedman methods were 145.78, 143.35, and 142.87 kJ/mol and pre-exponential factors ranged from 105 to 1011 indicating empirical first order reaction. Gibbs free energy change and entropy change varied from 184.43 to 187.21 kJ/mol and from −147.21 to −35.59 J/mol, representing disorderness of products were lower than that of the initial compound. The above kinetics, thermodynamics and HHV results, confirmed that ISS has enough potential to be a source bio-energy. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13131, 2019. © 2018 American Institute of Chemical Engineers